KAJIAN NILAI-NILAI KEARIFAN LOKAL PADA ARSITEKTUR HOTEL BINTANG DAN HUNIAN VERTIKAL DI KAWASAN CAGAR BUDAYA YOGYAKARTA - Muhammad Arief Kurniawan; Chyntyaningtyas Meytasari (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2019)
ABSTRACTYogyakarta City Government (Pemkot) and the surrounding Regency Government (Pemkab) get a lot of criticism from the public regarding policies that have resulted in massive vertical residential development in the form of hotels and apartments. In addition, the presence of vertical housing is also feared to have an impact on changes in community culture.This study aims to examine the extent to which local wisdom values are applied to star hotels and vertical occupancy in the Yogyakarta Cultural Heritage Area and what direction can be obtained so that star hotels and vertical housing are able to incorporate the value of local wisdom in YogyakartaThis research was conducted using the transforming tradition method. The main principles of the ATUMICS method are about regulation, combination, integration, or a mixture of basic elements of tradition with modernity.The results of the analysis found that the percentage of local wisdom in star hotels and vertical buildings in malioboro 8%, Kraton 15%, Puro Pakualaman 10%, Kotagede 30% and Kotabaru 5%. The average of all is 13.6%. This proves that the value of local wisdom in star hotels and vertical buildings is still low (below 50%). Most star hotels and vertical buildings have not adopted the type of architecture that suits their respective regions. The total stars and vertical buildings still display modern architecture and the present as the main architecture.Keywords: cultural heritage areas, star hotels, value of local wisdom, vertical residential